Defining a reference range for cold agglutinin titers. Issue 5 (16th October 2013) - Bendix, Brenda J.; Tauscher, Craig D.; Bryant, Sandra C.; Stubbs, James R.; Jacob, Eapen K.
<x xml:space="preserve">Abstract</x> Background The cold agglutinin (CAGG) titer is offered at our institution to aid in diagnosing cold agglutinin disease (CAD). Our goal was to create a seasonally adjusted reference range using prospective samples and compare it to a reference range generated retrospectively. Study Design and Methods Prospective CAGG titer testing was performed on healthy blood donors. Retrospective electronic analysis was performed on patients in two groups defined by current and historical testing methods. Blood donor testing was performed in January and July to determine if seasonal variation existed. Retrospective patients with conditions associated with CAD were excluded from analysis. Additional prospective CAGG testing using reference range program volunteers was performed to verify blood donor and patient result differences. Results Titers from the blood donor and patient cohorts had no age association (p > 0.44). Titers from those same cohorts did not show winter/summer variation (p > 0.11). No sex association was found with titer reference ranges in the blood donor and historical patient cohort. A sex association was found with titers in the current method patient cohort (male 64 to 512 and female ≤64; p < 0.0001). Blood donor CAGG titer lower 95% reference range was not more than 4 while historical and current patient cohorts ranges were not more than 32 and not more than 64, respectively. Reference range volunteers confirmed the narrow reference range in healthy individuals when compared to patients and blood donors. Conclusion Prospective blood donor CAGG titers were lower than retrospective patient cohorts. This may be due to blood donors representing a healthier population than the patient cohorts.